Determinants of Indonesian Government Bond Yields - Ganistie Furry Qisthina; Noer Azam Achsani; Tanti Novianti (School of Business, Bogor Agricultural University (SB-IPB), 2022)
An important factor that becomes a consideration for investors in purchasing bonds as an investment instrument is the bond yield. Bond yields are used to calculate how much income the investors will get in a certain period of time. The yield movement can be influenced by various factors. This study aims to analyze the effect of bond prices, BI rate, inflation, and exchange rates on medium-term (10 years) and long term (30 years) Indonesian government bond yields. Data used in this research were monthly time series data from January 2015 to December 2019. The time-series data were analyzed by VAR/VECM. The results of the study found that bond price had a significant negative effect on medium term and long term government bond yields. The interest rate had a significant positive effect on long term government bond yields and the exchange rate had a significant positive effect on medium term government bond yields. Inflation had no significant effect on medium and long term government bonds yields. The exchange rate made the greatest contribution to medium term government bond yield changes while long term government bond made the greatest contribution to bond prices. Keywords: BI rate, bond prices, exchange rates, inflation, bond yields